Sustainability of UAVs in developing countries: Prospects and challenges. (2nd January 2020) - Lalrochunga, David; Parida, Adikanda; Choudhury, Shibabrata
Abstract: Unmanned Aerial Vehicle (UAV) or generally well known as drones created opportunities in socio-economic development in developing countries. Augmenting these technologies through capturing accurate and real time data in a cost effective way created prospects and challenges of UAV. However, the types, policies that govern their flying altitudes and the technology will be required to regulateand monitor these flying machines, which do not carry human operators and fly autonomously in reference to the developing countries is discussed.